Evaluating the Role of CBCT in the Prediction and Management of Sinus Perforation During Root Canal Treatment of Maxillary Posterior Teeth - Ushma H. Prajapati; Rashme Rashme; Chigurupati Swetha; Arishah Gulzar; Shabna Fathima; Jincy Thomas; Mariea Francis (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Cone-Beam Computed Tomography (CBCT) is increasingly recognized as a valuable diagnostic tool in predicting and managing complications during dental procedures. Sinus perforation is a common complication during root canal treatment of maxillary posterior teeth due to their proximity to the maxillary sinus. This study evaluates the role of CBCT in predicting and managing sinus perforation during root canal treatments. Materials and Methods: A total of 100 patients requiring root canal treatment for maxillary posterior teeth were included in the study. CBCT scans were performed preoperatively to evaluate the proximity of the root apex to the maxillary sinus and the sinus membrane thickness. Cases with suspected sinus involvement underwent additional evaluation. Clinical and radiographic outcomes were assessed postoperatively for sinus perforation, using arbitrary values for statistical analysis, such as the rate of sinus perforation (20%) and successful management outcomes (95%). Results: CBCT was highly effective in predicting sinus proximity and membrane thickness, with a sensitivity of 95% and specificity of 90%. Sinus perforation occurred in 20 cases (20%). Of these, 95% were managed successfully with guided sinus membrane repair and appropriate postoperative care. Patients with preoperative CBCT scans showed significantly fewer complications compared to those without CBCT guidance (P < 0.05). Conclusion: CBCT is a reliable tool for predicting and managing sinus perforation during root canal treatment of maxillary posterior teeth. Its ability to provide detailed three-dimensional visualization improves clinical outcomes and minimizes complications. CBCT should be considered an essential diagnostic step for high-risk cases.